Silencing of spontaneous activity at α4β1/3δ GABA(A) receptors in hippocampal granule cells reveals different ligand pharmacology - Dalby, Nils Ole (Br J Pharmacol, 2020)
BACKGROUND AND PURPOSE: The δ‐subunit‐containing GABA(A) receptors, α(4)β(1)δ and α(4)β(3)δ, in dentate gyrus granule cells (DGGCs) are known to exhibit both spontaneous channel openings (i.e. constitutive activity) and agonist‐induced current. The functional implications of spontaneous gating are unclear. In this study, we tested the hypothesis that constitutively active α(4)β(1/3)δ receptors limit agonist efficacy. EXPERIMENTAL APPROACH: Whole‐cell electrophysiological recordings of adult male rat and mouse hippocampal DGGCs were used to characterize known agonists and antagonists at δ‐subunit‐containing GABA(A) receptors. To separate constitutive and agonist‐induced currents, different recording conditions were employed. KEY RESULTS: Recordings at either 24°C or 34°C, including the PKC autoinhibitory peptide (19–36) intracellularly, removed spontaneous gating by GABA(A) receptors. In the absence of spontaneous gating, DGGCs responded to the α(4)β(1/3)δ orthosteric agonist Thio‐THIP with a four‐fold increased efficacy relative to recording conditions favouring constitutive activity. Surprisingly, the neutral antagonist gabazine was unable to antagonize the current by Thio‐THIP. Furthermore, a current was elicited by gabazine alone only when the constitutive current was silenced (EC(50) 2.1 μM). The gabazine‐induced current was inhibited by picrotoxin, potentiated by DS2, completely absent in δ(−/−) mice and reduced in β(1) (−/−) mice, but could not be replicated in human α(4)β(1/3)δ receptors expressed heterologously in HEK cells. CONCLUSION AND IMPLICATIONS: Kinase activity infers spontaneous gating in α(4)β(1/3)δ receptors in DGGCs. This significantly limits the efficacy of GABA(A) agonists and has implications in pathologies involving aberrant excitability caused by phosphorylation (e.g. addiction and epilepsy). In such cases, the efficacy of δ‐preferring GABA(A) ligands may be reduced.